Stability of formoterol concentration in scalp hair of patients using maintenance formoterol therapy for asthma or COPD (INCTFISH) - Sportel, E.; Wagelaar, K.; Brusse-Keizer, M.; van der Palen, J.; van Veen, H.; Wessels, M.; van Boven, J.; Touw, D.; Movig, K. (Frontiers in Pharmacology, 2025)
IntroductionHair testing provides a non-invasive, objective method with a long (retrospective) surveillance window for assessing medication adherence. Previous studies have developed a method to analyze formoterol in hair and suggest a possible dose-response relationship. The INCTFISH study aims to assess the stability of formoterol concentrations in hair in patients using formoterol for asthma or COPD maintenance therapy.MethodsIn total, 13 subjects ≥18 years of age, with asthma or COPD, who demonstrated stable to intermediate adherence and medication possession ratio, were included in this pilot study. To study the stability of formoterol, two hair segments located at one and 3 cm from the patient’s scalp were collected, corresponding to a time frame of approximately 3 months. Scalp hair samples were taken during a study visit and analyzed using Liquid Chromatography-Tandem Mass Spectrometry.ResultsInhaled formoterol was detected in most hair samples with all hair colors in a concentration range of 0.73–7.6 ng/g. The intraclass correlation between segment one and two was excellent (ICC = 0.97).DiscussionThe pilot study reveals a strong correlation between formoterol concentrations in segment one and two, indicating that drug levels remain stable in hair over a period of at least 3 months. While the study does not yet provide sufficient evidence to establish the utility of hair testing for monitoring formoterol adherence, it provides important directions for future research.